THE BROKEN CEO How To Be The Leader You Always Wanted To Be - Chris Pearse (Great Britain ‎ Independently published, 2020)
Do you long to transform the stress, conflict and survival of leadership into fulfilment, meaning and success? Are you tired of always running but never arriving? Do you yearn for another way of working and leading?
Keywords: Self leadership